A dual role of tobacco hexokinase 1 in primary metabolism and sugar sensing - Kim, Young-Min; Heinzel, Nicolas; Giese, Jens-Otto; Koeber, Julia; Melzer, Michael; Rutten, Twan; Von Wiren, Nicolaus; Sonnewald, Uwe; Hajirezaei, Mohammad-Reza (Plant Cell and Environment, 2013)
Hexokinase (HXK) is present in all virtually living organisms and is central to carbohydrate metabolism catalysing the ATP-dependent phosphorylation of hexoses. In plants, HXKs are supposed to act as sugar sensors and/or to interact with other enzymes directly supplying metabolic pathways such as glycolysis, the nucleotide phosphate monosaccharide (NDP-glucose) pathway and the pentose phosphate pathway. We identified nine members of the tobacco HXK gene family and observed that among RNAi lines of these nine NtHXKs, only RNAi lines of NtHXK1 showed an altered phenotype, namely stunted growth and leaf chlorosis. NtHXK1 was also the isoform with highest relative expression levels among all NtHXKs. GFP-tagging and immunolocalization indicated that NtHXK1 is associated with mitochondrial membranes. Overexpression of NtHXK1 resulted in elevated glucose phosphorylation activity in leaf extracts or chloroplasts. Moreover, NtHXK1 was able to complement the glucose-insensitive Arabidopsis mutant gin2-1 suggesting that NtHXK1 can take over glucose sensing functions. RNAi lines of NtHXK1 showed severely damaged leaf and chloroplast structure, coinciding with an excess accumulation of starch. We conclude that NtHXK1 is not only essential for maintaining glycolytic activity during respiration but also for regulating starch turnover, especially during the night.
Keywords: Arabidopsis thaliana; Nicotiana tabacum; gin2-1; hexokinase; starch metabolism